Nab-Paclitaxel, cisplatin, and 5-fluorouracil followed by concurrent cisplatin and radiation for head and neck squamous cell carcinoma. (October 2016) - Adkins, Douglas; Ley, Jessica; Michel, Loren; Wildes, Tanya M.; Thorstad, Wade; Gay, Hiram A.; Daly, Mackenzie; Rich, Jason; Paniello, Randal; Uppaluri, Ravindra; Jackson, Ryan; Trinkaus, Kathryn; et al.
Highlights: Phase II trial: nab -paclitaxel, cisplatin and 5-FU (APF) followed by CRT. Two-year DSS (97%) and OS (93%) were excellent. Relapse rate was very low (3%). Abstract: Objectives: We previously reported the efficacy of nab -paclitaxel added to cisplatin, 5-FU, and cetuximab (APF-C) followed by concurrent high dose bolus cisplatin and radiation therapy (CRT) in patients with locally advanced head and neck squamous cell carcinoma (HNSCC). In this phase II trial, we determined the efficacy of APF (without cetuximab) followed by CRT in similar patients. Materials and methods: Eligible patients had stage III–IV oropharynx (OP), larynx, or hypopharynx SCC and adequate organ function and performance status. T1 tumors were excluded. Patients were treated with three cycles of APF followed by CRT. Efficacy endpoints included two-year disease-specific survival (DSS), progression-free survival (PFS), overall survival (OS), and relapse rate. Results: Thirty patients were enrolled. Most patients were smokers (77%) with bulky T3/4 (73%) and N2/3 (83%) tumors. Analyses were stratified for human papilloma virus (HPV) status: HPV-related OPSCC (n = 17; 57%) and HPV-unrelated HNSCC (n = 13; 43%). With a minimum follow-up of 21 months, relapse occurred in 1 (3%) patient. Two-year DSS was 94% in HPV-related OPSCC and 100% in HPV-unrelated HNSCC. Two-year PFS was 94% in HPV-related OPSCC and 100% in HPV-unrelated HNSCC. Two-year OS was 94% in HPV-related OPSCC and 92% in HPV-unrelated HNSCC. Causes of death were relapse (1), treatment-related mortality (1), and co-morbidity (1). Two patients with HPV-unrelated HNSCC treated with APF declined CRT and remained free of relapse at 36 and 28 months of follow-up. Conclusion: This phase II trial demonstrated favorable two-year DSS, PFS, and OS and a low relapse rate in HPV-unrelated HNSCC and HPV-related OPSCC treated with APF followed by CRT.